Dionysius on the Problem of Evil: Lessons One can Learn - Joseph, Jijimon Alakkalam (Tattva Journal of Philosophy, 2015)
The problem of evil is a much-debated issue and is as old as human history itself. Evil is a universal and the most common experience of humans, in the sense it functions as a common denominator and no one escapes. Evil causes a sense of isolation. This is evident in the lives of theists. Evil isolates humans from God. Evil is also one such experience that is personal and existential. Evil brings along a lot of meaninglessness. Here it expresses itself as victimization.